Efficacy and safety of empagliflozin in people with type 2 diabetes during Ramadan fasting. Issue 11 (November 2022) - Yousuf, Sanobia; Ahmedani, Muhammad Yakoob
Abstract: Background and aims: To explore efficacy and safety of empagliflozin in people with type2 diabetes during Ramadan fasting Methods: People with type2 diabetes (T2DM) who were taking empagliflozin and sulphonylurea with or without a metformin and dipeptidyl peptidase inhibitors (DPP4) recruited a month before Ramadan. Glycated hemoglobin (HbA1c) and estimated glomerular filtration rate (eGFR) were recorded pre- and post-Ramadan. A predesigned diary was given to the participants to keep track of their T2DM status during Ramadan. The proportion of the people who had hypoglycaemia, or any adverse event related to the study drug was assessed after-Ramadan. Results: A total of 116 participants completed the study. Symptomatic episodes of hypoglycaemia were more common among people who used sulphonylurea (i.e., 8.6%). Genitourinary infections and volume depletion events were recorded more in people on empagliflozin i.e., (6.9% and 5.17%, respectively). A significant reduction in body mass index (BMI), and HbA1c was noted among people on empagliflozin post Ramadan. A significant reduction in eGFR was noted only in people who were taking empagliflozin in combination with metformin. Conclusion: Empagliflozin was found to be safe and effective in fasting people with T2DM. Further large-scale studies are needed to validate our findings. Highlights: Empagliflozin was found to be safe and effective in fasting people with diabetes. Participants who took empagliflozin experienced significant weight loss. Better glycemic control was observed with empagliflozin than sulphonylurea therapy.